2021
DOI: 10.1101/2021.05.29.21258043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new method to measure inter-breath intervals in infants for the assessment of apnoea and respiratory dynamics

Abstract: Background Respiratory disorders, including apnoea, are common in preterm infants due to their immature respiratory control and function compared with term-born infants. However, our inability to accurately measure respiratory rate in hospitalised infants results in unreported episodes of apnoea and an incomplete picture of respiratory dynamics. Methods We develop, validate and use a novel algorithm to identify inter-breath intervals (IBIs) and apnoeas in infants. In 42 infants (a total of 1600 hours of recor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…Using these methods could improve apnoea detection and consequently our understanding of apnoea in preterm infants; 74% of apnoeic events across 276 infants identified using the algorithm of Lee et al were not documented in clinical notes ( 94 ). Similarly, in our study we found that 88% of apnoeas were missed in clinical notes ( 93 ).…”
Section: Improvements In Aop Measurementsupporting
confidence: 78%
See 1 more Smart Citation
“…Using these methods could improve apnoea detection and consequently our understanding of apnoea in preterm infants; 74% of apnoeic events across 276 infants identified using the algorithm of Lee et al were not documented in clinical notes ( 94 ). Similarly, in our study we found that 88% of apnoeas were missed in clinical notes ( 93 ).…”
Section: Improvements In Aop Measurementsupporting
confidence: 78%
“…Lee et al ( 91 ) developed a new method for the detection of apnoea from the impedance pneumograph by first removing cardiac interference. Our group recently built on this work and developed a new method to identify inter-breath intervals and apnoeas in infants which included an automated classifier to distinguish between periods of true apnoea and signal which is low amplitude due to artefacts or poor electrode placement ( 93 ). Using these methods could improve apnoea detection and consequently our understanding of apnoea in preterm infants; 74% of apnoeic events across 276 infants identified using the algorithm of Lee et al were not documented in clinical notes ( 94 ).…”
Section: Improvements In Aop Measurementmentioning
confidence: 99%
“…For example, we have recently developed an algorithm to better identify inter‐breath intervals and episodes of apnea from the chest electrical impedance pneumograph; using this we found that 88% of apneas (defined as pauses in breathing of at least 20 seconds) identified using our method were not recorded on clinical notes and demonstrated a significant increase in pauses in breathing of at least 10 seconds following retinopathy of prematurity screening, which is not reflected in clinical notes or in changes in the respiratory rate recorded directly on the monitor. 34 Similarly, Vergales et al found that more than 70% of apneas (of duration of at least 30 seconds and accompanied by bradycardia and desaturation) identified using an algorithm developed by their group were missed in clinical notes. 33 This highlights the importance of using vital signs recordings directly rather than clinical records and the improvements that could be made in personalized drug dosing through detailed analysis of vital signs compared with clinical intermittent observations of the data.…”
Section: Vital Signs—an Underutilized Resource?mentioning
confidence: 98%
“…28 , 29 While some neonatal units are now storing electronic records of these data, in many hospitals it is not saved, and instead nursing observations of events such as episodes of oxygen desaturation, bradycardia and tachycardia, are recorded on clinical charts allowing for review of trends in an infant's data. These records will document the most severe episodes of physiological instability but provide only an intermittent and somewhat subjective view of the infant's physiology, 30 will miss more subtle changes in an infant's vital signs that may be caused by pharmacological interventions, may be unreliable due to known problems in vital signs monitoring (particularly with regard to missing episodes of apnea due to cardiac interference on respiratory recordings), 31 , 32 , 33 , 34 and do not allow for more complex analysis that may reveal important predictive features within the data. For example, we have recently developed an algorithm to better identify inter‐breath intervals and episodes of apnea from the chest electrical impedance pneumograph; using this we found that 88% of apneas (defined as pauses in breathing of at least 20 seconds) identified using our method were not recorded on clinical notes and demonstrated a significant increase in pauses in breathing of at least 10 seconds following retinopathy of prematurity screening, which is not reflected in clinical notes or in changes in the respiratory rate recorded directly on the monitor.…”
Section: Vital Signs—an Underutilized Resource?mentioning
confidence: 99%
“…67 68 Exploratory outcome measures will also include the time taken for the heart rate to return to baseline values post heel lance and respiratory rate variability in the 30 min prior and post heel lance (including incidence of apnoea). An episode of apnoea will be defined as the cessation of breathing for at least 20 s. 69 Parental experience Parental anxiety will be quantified using the outcomes of the STAI-T and STAI-S questionnaires. Parental distress will be quantified using the four-point distress score.…”
Section: Clinical Stabilitymentioning
confidence: 99%